Investigations on reaction rates adapted to a secondary chemistry course - Sison, Lilian de Jesus- 1947- (1976)
The purpose of the study was to investigate the reactivity of metals with hydrochloric acid, with the aim of devising a laboratory activity on reaction rates adapted to a secondary chemistry course. The researcher found out that the experiments are economical and can easily be duplicated in as much as the materials used are readily available in a typical barangay school. The experimental results were found to be reliable, consistent and reproducible within certain limits.
"December, 1976."
Vita.
Thesis (M.A.T. Chemistry)--University of the Philippines, Diliman.
Keywords: Reaction mechanisms (Chemistry).; Hydrochloric acid; Chemistry -- Study and teaching (Secondary) -- Philippines